(untitled) (Annals of Medical Research, 2022)
Aim: The aim of the study is to evaluate the relationship between age and leukocyte subtype ratio and their effects on survival in patients diagnosed with myelodysplastic syndrome (MDS). Methods: We retrospectively examined total of 101 patients diagnosed with MDS between January 2010 and June 2020. The patients were analysed by dividing into two groups; <70 years and ≥70 years. Results: The median of overall survival was significantly higher in <70 years group (96 vs 40 month, OR 3,6; 95% CI, 1,6-8,7, p<0,001). Whereas neutrophil-to-lymphocyte ratio (NLR) was significantly higher in ≥70 years group, lymphocyte-to-monocyte ratio (LMR) was significantly higher in <70 years group (p= 0,013 and p= 0,041, respectively). NLR was positively correlated with age (rho: 0,27, p= 0,007) but negatively correlated with clinical risk (rho: -0,24, p= 0,018), MPV/PLT ratio was positively correlated with IPSS group (rho: 0,40, p<0,001). In multivariate analysis, its found that age and IPSS group effects overall survival. HR was 1,064 (95% CI; 1,033-1,096, p<0,001) for age and was 3,664 (95% CI; 1,285-10,445, p<0,015) for IPSS group (low versus intermediate-2). Conclusion: We concluded that NLR and LMR may have a prognostic value for patients who are ≥70 years diagnosed MDS.